2014
DOI: 10.1074/jbc.m113.488593
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA HOTAIR Is Targeted and Regulated by miR-141 in Human Cancer Cells

Abstract: Background: Silencing of long non-coding RNA (lncRNA) by microRNA (miRNA) has only been recently observed. Results: miR-141 binds to HOTAIR and suppresses its oncogenic function in Ago2 (Argounaute2). Conclusion: miR-141 targets and silences HOTAIR in an Ago2-dependent manner in cancer cells. Significance: Our results suggest that regulation of lncRNA expression by miRNA plays essential roles in gene expression and cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 62 publications
6
152
0
1
Order By: Relevance
“…It was enough to demonstrate that the instability of this circular ncRNA was directly related to miRNA-671 [15]. Furthermore, the well-characterized lncRNA HOTAIR was reported to be repressed by miRNA-141 in the presence of the Ago2 complex in human cancer cells [45]. Another study also demonstrated that lncRNA HOTAIR was degraded jointly by HuR, miRNA-let7i and Ago2 [46], and lncRNA MALAT1 was testified to be downregulated by has-miR-125b during bladder cancer development [47].…”
Section: Post-transcriptional Regulation Of Lncrnasmentioning
confidence: 94%
“…It was enough to demonstrate that the instability of this circular ncRNA was directly related to miRNA-671 [15]. Furthermore, the well-characterized lncRNA HOTAIR was reported to be repressed by miRNA-141 in the presence of the Ago2 complex in human cancer cells [45]. Another study also demonstrated that lncRNA HOTAIR was degraded jointly by HuR, miRNA-let7i and Ago2 [46], and lncRNA MALAT1 was testified to be downregulated by has-miR-125b during bladder cancer development [47].…”
Section: Post-transcriptional Regulation Of Lncrnasmentioning
confidence: 94%
“…HOTAIR was reported to be induced by E 2 in MCF-7 BCa cells (Bhan, et al 2013), but others reported that E 2 -ERα directly that repressed HOTAIR in MCF-7 cells by binding to a genomic site 14.5 kB upstream of HOTAIR (Xue, et al 2016b). HOTAIR is downregulated by miR-141 (Chiyomaru, et al 2014) and is directly targeted by miR-34a in PCa cells (Chiyomaru, et al 2013). The 3' domain of HOTAIR binds lysine-specific demethylase 1 (LSD1)-CoREST and PRC2 interacts with a 5' domain.…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
“…Owing to this function, HOTAIR overexpression in cancer leads to genome-wide changes in the chromatin-modifying complex binding sites. Interestingly, HOTAIR expression was recently reported to be inversely correlated with miR-141 expression in renal carcinoma cells (Chiyomaru et al, 2014). In essence, HOTAIR promotes malignancy, including proliferation and invasion, whereas miR-141 functions as a tumor suppressor.…”
Section: Intergenic Lncrnasmentioning
confidence: 99%